The effect of oxalic acid as a doping agent on the conductivity of polyaniline / Amirah Amalina Ahmad Tarmizi … [et al.] - Ahmad Tarmizi, Amirah Amalina; Harun, Mohamad Kamal; Abdullah, Saifollah; Bahron, Hadariah; Yahya, Muhd Zu Azhan; M. Yahaya, Sabrina; Abdul Halim, Nurul Huda (Penerbit UiTM (UiTM Press), 2016)
This study investigates the effect of oxalic acid at different concentrations as doping agent on the electrical properties of polyaniline (PANI). The polymerization of aniline to produce PANI was carried out in media containing oxalic acid at 0.08 M, 0.09 M, 0.1 M, 0.2 M and 0.3 M in the presence of ammonium persulphate as oxidizing agent. The successful formation of PANI doped with oxalic acid was confirmed by FTIR and the morphology studied using XRD. An impedance investigation on the series of PANI formed revealed that doping in 0.1 M oxalic acid produced PANI of the highest conductivity of 2.52 x 10⁻⁶ Scm⁻¹.